Los vertebrados del Tithónico-Barremiense de Galve (Teruel, España) - Meléndez, Alfonso; Amo, O.; Canudo, J.I.; Cuenca-bescós, G.; Ruiz-omeñaca, J.I.; Soria, Ana Rosa (Cuadernos de Geología Ibérica, 1997)
Sin resumen